(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The research has aimed to study the effect of treatment with bio-fertilizer "EM1" on the growth and yield of green beans (Phaseolus vulgaris L.). The research was conducted during the spring of the agricultural season 2022 in the village of Nahr-Al Arab (Lattakia countryside). The "Tema" variety of beans was used in its conduct. The experiment included four treatments: control (untreated plants), and plants treated with "EM1" at three concentrations (5-7 -10) cm3 Ł. Randomized complete blocks design was used in conducting the research with three replicates per treatment, and 15 plants in each replicate. The results showed that the treatment with the bio-fertilizer of the concentration of 10 cm3 Ł achieved the best results and the highest values in all the studied parameters. In the observations of the vegetative growth, plant height was recorded as (35.1 cm), the number of leaves (28.5) leaf/plant, total leaf area (5469.1 cm2), and area index leaf (5.46). In the observations of the fruit growth, the number of flowers was recorded as (117.7 flowers/ plant), set percentage (81.6%). In the productivity observations, the production of the plant was recorded as (672 g/plant) with a relative efficiency of (84.9%).